2004
DOI: 10.1080/09637480412331290512
|View full text |Cite
|
Sign up to set email alerts
|

Effect of temperature on soluble invertase activity, and glucose, fructose and sucrose status of onion bulbs (Alliumcepa) in store

Abstract: The activity of soluble invertase, and the variation in glucose, fructose and sucrose contents in onion bulbs (Allium cepa) during long-term storage at 10 degrees C and 20 degrees C were investigated. Invertase activity increased progressively after 8 weeks to 0.084 and 0.092 nkat/g fresh weight (FW), then sharply to 0.29 and 0.35 nkat/g FW at 20 degrees C and 10 degrees C, respectively, and remained high during 5 weeks. Then, activity decreased abruptly to 0.039 and 0.041 nkat/g, and remained low during the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
14
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 20 publications
4
14
0
Order By: Relevance
“…Our repeated experiments on this point concludes sucrose is deviated from glucose and fructose. Further, the metabolism of sucrose into glucose and fructose catalysed by the enzyme invertase is largely independent of temperature and depends on the physiology of onion (Benkeblia et al 2004). Also, a similar behavior has been reported by Chope et al 2007a, where the trend of fructose and glucose correlative and the sucrose level varying differently.…”
Section: Sugars Contentsupporting
confidence: 55%
See 1 more Smart Citation
“…Our repeated experiments on this point concludes sucrose is deviated from glucose and fructose. Further, the metabolism of sucrose into glucose and fructose catalysed by the enzyme invertase is largely independent of temperature and depends on the physiology of onion (Benkeblia et al 2004). Also, a similar behavior has been reported by Chope et al 2007a, where the trend of fructose and glucose correlative and the sucrose level varying differently.…”
Section: Sugars Contentsupporting
confidence: 55%
“…Our results are in contrast with , where they noticed continuous decrease in quercetin glucosides during the storage of 168 days. Previously it was reported Benkeblia et al (2004) total phenolic content of inner buds for control sample (stored at 18°C) increased during 5th week and then decreased progressively during last 3 weeks of storage. On the contrary, Gennaro et al (2002) reported that for flavonoids in red onion tends to decrease after 6 weeks storage especially at 20°C and 30°C.…”
Section: Flavonoids Contentmentioning
confidence: 99%
“…It has been previously reported that heat treatment of garlic extract resulted in the highest antibacterial activity and that this positively correlates with increases in DAS content as evidenced by GC and mass spectrometric analyses (11,15,42,65). Recently, the inhibitory mechanism of DAS against Listeria monocytogenes and E. coli O157:H7 was demonstrated by Fourier transform infrared (FT-IR) and Raman spectroscopy (54).…”
Section: Discussionmentioning
confidence: 99%
“…Garlic has been used as a medicine since ancient times and has long been known to have antibacterial, antiviral, antifungal, antialgal, antiproteolytic, anticancer, antithrombotic, antiatherosclerotic, antioxidant, and immune modulation properties (4,5,12,16,45,58,59,60,66,69,70,77). Recently, garlic extract was shown to have effective broad-spectrum antimicrobial activity (11,15,21,44,62,74), including activity against oral bacteria (8). The main antimicrobial constituent of garlic has been identified as the oxygenated sulfur compound allicin.…”
mentioning
confidence: 99%
“…Post-harvest metabolism of fructo-oligosaccharides in onion and asparagus plants Alongside the studies on fructo oligodsaccharide accumulation during seed development 36) and bulbing, 37) we also studied the main enzyme activities involved in the synthesis and the hydrolysis of fructo oligosaccharides during the pre harvest 38) (growth), and post harvest 38,39) (storage) life of onion bulbs and asparagus spears, 40) although present knowledge is insufficient to clearly explain the mechanisms triggering enzymes or the mechanisms by which fructo oligosaccharides contribute to bulb quality and perishability. 39) Storage of onion bulbs for 6 months causes a decrease 41,42) in the contents of glucose, fructose and sucrose, as shown by Fig. 15.…”
Section: Enzymatic Preparation Of Fructo-oligosaccharidesmentioning
confidence: 99%